ANALYSIS OF WATER SPINACH AGRIBUSINESS APPLICATION IN BORDER AREA OF REPUBLIC OF INDONESIA – DEMOCRATIC REPUBLIC OF TIMOR LESTE - Robertus H. Nule; Agustinus Nubatonis; umbu joka (AGROLAND The Agricultural Sciences Journal (e-Journal), 2021)
This study aimed to find out the general description, analyze the level of application, and determine the income of the kale agribusiness in Napan Village. This research was conducted at the Bikiu Farmer Group, Napan Village, North Bikomi District. Data collection was carried out in August 2020. Sampling was carried out using a purposive sampling method, which only took all group members. The data collected in the form of primary and secondary data were then tabulated using income analysis and R/C ratio to determine the feasibility of water spinach farming. The results of the study concluded that the stages of water spinach farming activities with an area of ​​15 hectares with each group member entitled to 5 acres, with a total fixed cost of Rp. 2,509,374.5 or the average fixed cost incurred is Rp. 167.291.7 -/ha. The total variable costs incurred are Rp. 400,000, with an average variable cost of Rp. 26,666.67,-/ha, the total income obtained by farmers in water spinach cultivation activities is Rp. 36,294,625, - with an average income of Rp.1,960.2 00, with total income is Rp. 36,294,625, with an average income of Rp. 2,419,642., -/ha for one planting season. The feasibility of water spinach vegetable farming (R/C Ratio) obtained by farmers is 13.47. Water spinach farming is profitable, so it is feasible to continue.